Synthesis and Biological Studies of Some Cu(II) Macrocyclic Complexes - Ambwani, Jitendra; Bansal, N.L.; Kaushik, Kshama (Asian Journal of Chemistry, 2010)
Two new macrocyclic complexes have been synthesized by con- densing dithio-dipropionic acid dihydrazone with 2,6-diacetyl pyridine/2,6- pyridine dicarbonyl dichloride in presence of Cu(II) ions. The complexes have the formulae Cu[DPDTDPH](BF4)2 and Cu[DCDTDPH](BF4)2 (where [DPDTDPH] = 2,6-diacetyl pyridine dithio dipropionic acid dihydrazone and [DCDTDPH] = 2,6- pyridine dicarbonyl dichloride-dithio-dipropionic acid dihydrazone. The in vitro antimicrobial studies revealed that the macrocyclic complexes are potentially active against a few bacteria and fungi and exhibit greater biocidal effect as compared to the ligand fragments. The synthesized complexes have been characterized by elemental studies, conductivity measurements and spectral (IR and electronic) studies.